PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN KONSUMEN PENGGUNA LAYANAN JASA ANTAR MAKANAN (GOFOOD) DI KOTA CIREBON - Febianti, Yopi Nisa; Welly, Welly (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
One of the businesses developed by Gojek is Go-food. Go-food is a service feature provided by Gojek which provides food delivery services. Go-food services provide convenience in terms of mobility and the food ordering process. Apart from that, the simple payment system also makes Go-food a favorite choice among the public. This research aims to determine the effect of service quality on the level of satisfaction of users of food delivery services (Go-Food) in Cirebon City. Quality in this context includes aspects such as delivery speed, order accuracy, food quality, and customer service availability. This research uses a survey method by distributing questionnaires to Go-Food users in Cirebon City. The population of this research is people in the Cirebon City area who have used Go-Food services) with an unknown population size. The sampling technique uses purposive sampling. Using questionnaire data collection techniques. Test analysis uses multiple linear regression tests. The results of the analysis show that service quality has a significant positive effect on the level of satisfaction of Go-Food service users in Cirebon City. This means that the higher the quality of service provided by the company, the higher the satisfaction that consumers will feel.